The cost analysis of a leading optics business in Saudi Arabia. (8th February 2021) - Bakhsh, Ahmed A.
This study aims to use discrete event simulation (DES) to minimise the processing cost of a leading optics business in Saudi Arabia. Data is collected from three branches to calculate the operating cost and delivery time of the products. A proposed solution is developed to replace three technical workshops inside every branch with one central workshop in the city. Numbers of replications are carried out to reach the optimal solution. Cost analysis is done to compare the process cost, delivery time and idle working hours of the two options. A significant reduction is observed in the process cost and delivery time of the products besides increasing the idle working hours of the technicians. These improvements can be utilised to enhance the productivity and profitability of the organisations.